Monsoon intra-seasonal variability in a high-resolution version of Met Office Global Coupled model - Yongjie Fang; Peili Wu; M.S. Mizielinski; M.J. Roberts; Bo Li; Xiaoge Xin; Xiangwen Liu (Tellus: Series A, Dynamic Meteorology and Oceanography, 2017)
Intra-seasonal oscillation (ISO) is a key ingredient of the East Asia and western North Pacific (EAWNP) summer monsoon and particularly important for seasonal forecast. This paper evaluates the seasonal means and ISOs of the EAWNP summer monsoon simulated by the latest version of the Met Office Global Coupled Model (HadGEM3-GC2) with two different atmospheric model resolutions at ~130 and ~25 km coupled to a same 0.25° × 0.25° resolution ocean model. Results show that the mean states of sea surface temperature (SST), low-level specific humidity and the western Pacific subtropical high are all improved in HadGEM3-GC2 with higher atmosphere resolution. Moreover, although ISO variance is overestimated over the western North Pacific, the model has good fidelity in characterising ISO basic features over the EAWNP including the dominant EOF structure, northward propagation and cycle evolution, as well as the zonal displacement of western Pacific Subtropical High and South Asian High associated with the northward propagating ISOs. Increasing atmosphere model resolution yields improvements in most aspects of the Monsoon ISO over the EAWNP, especially for its northward propagation. Further analysis indicates that this improvement is mainly due to the better description of ISO-related air–sea interaction in higher resolution experiment, as evidenced by the enhanced intra-seasonal SST variance and more coherent northward propagation of rainfall, SST, and the associated surface dynamic and thermodynamic variables in the higher resolution model.